Direct attenuation correction for 99mTc-3PRGD2 chest SPECT lung cancer images using deep learning - Xing, Haiqun; Wang, Tong; Jin, Xiaona; Tian, Jian; Ba, Jiantao; Jing, Hongli; Li, Fang (Frontiers in Oncology, 2023)
Introduction: The attenuation correction technique of SPECT images is essential for early diagnosis, therapeutic evaluation, and pharmacokinetic studies of lung cancer. 99mTc-3PRGD2 is a novel radiotracer for the early diagnosis and evaluation of treatment effects of lung cancer. This study preliminary discusses the deep learning method to directly correct the attenuation of 99mTc-3PRGD2 chest SPECT images. Methods: Retrospective analysis was performed on fifty-three patients with pathological diagnosis of lung cancer who received 99mTc-3PRGD2 chest SPECT/CT. All patients' SPECT/CT images were reconstructed with CT attenuation correction (CT-AC) and without attenuation correction (NAC). The CT-AC image was used as the reference standard (Ground Truth), to train the attenuation correction (DL-AC) SPECT image model using deep learning. 48 of 53 cases were divided randomly into the training set, the remaining 5 were divided into the testing set. Using 3D Unet neural network, the mean square error loss function (MSELoss) 0.0001 was selected. A testing set is used to evaluate the model quality, using the SPECT image quality evaluation and quantitative analysis of lung lesions tumor-to-background (T/B). Results: SPECT imaging quality metrics between DL-AC and CT-AC including mean absolute error (MAE), mean-square error (MSE), peak signal-to-noise ratio (PSNR), structural similarity (SSIM), normalized root mean square error (NRMSE) and Normalized Mutual Information (NMI) of the testing set are 2.62 ± 0.45, 58.5 ± 14.85, 45.67 ± 2.80, 0.82 ± 0.02, 0.07 ± 0.04, and 1.58 ± 0.06, respectively. These results indicate PSNR > 42, SSIM > 0.8 and NRMSE < 0.11. Lung lesions T/B (maximum) of CT-AC and DL-AC group are 4.36 ± 3.52 and 4.33 ± 3.09 (P = 0.81). There are no significant differences between two attenuation correction methods. Conclusions: Our preliminary research results indicate that using the DL-AC method to directly correct 99mTc-3PRGD2 chest SPECT images is highly accurate and feasible, for SPECT without configuration with CT or treatment effect evaluation using multiple SPECT/CT scans.